2021
DOI: 10.1007/s00240-021-01290-2
|View full text |Cite
|
Sign up to set email alerts
|

Diet-related urine collections: assistance in categorization of hyperoxaluria

Abstract: Hyperoxaluria, one of the major risk factors for calcium oxalate urolithiasis and nephrocalcinosis, causes significant morbidity and mortality and should therefore be detected and treated as soon as possible. An early, consequent and adequate evaluation, but also a distinction between primary (PH) and secondary hyperoxaluria (SH) is therefore essential. We evaluated the usefulness of three consecutive 24-h urine collections under different diets [usual diet, (A), low oxalate diet, (B), high oxalate diet, (C)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…Similar results were found by Dill et al. ( 2022 ) who mentioned that a low‐oxalate diet is helpful in the reduction of creatinine level. Low‐oxalate diet maintains the creatinine level at a normal range.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were found by Dill et al. ( 2022 ) who mentioned that a low‐oxalate diet is helpful in the reduction of creatinine level. Low‐oxalate diet maintains the creatinine level at a normal range.…”
Section: Resultssupporting
confidence: 88%
“…The result of this study showed a significant (p = .000) decrease in creatinine levels with the help of a low-oxalate diet as shows in Table 3. Similar results were found by Dill et al (2022) who mentioned that a low-oxalate diet is helpful in the reduction of creatinine level. Low-oxalate diet maintains the creatinine level at a normal range.…”
Section: Creatinine Levelssupporting
confidence: 88%
See 1 more Smart Citation
“…Radiolabeled isotope studies confirm that the kidneys mainly excrete oxalate (>90%), which is a highly insoluble end-product of human metabolism [4,5]. Glomerular filtration and tubular net secretion maintain a physiological oxalate excretion range of 10-40 mg/day (0.1-0.45 mmol/day); however, PH patients exhibit oxalate excretion exceeding 40-45 mg/day (0.45-0.5 mmol/day), accompanied by various systemic manifestations [6,7]. The deposition of calcium oxalate (CaOx) in the renal tubules and interstitium in PH can cause chronic tubulointerstitial inflammation and kidney stone obstruction, resulting in renal failure in over 70% of cases [8].…”
Section: Introductionmentioning
confidence: 99%